A geoelectrical survey above an Antarctic ice shelf - Merlanti, F.; Pavan, M. (Annals of Geophysics, 1998)
A geoelectrical survey was performed on the Hells Gate ice shelf (Victoria Land-Antarctic) within the framework of an integrated geophysical and glaciological research program. The resistivity profiles show a similar trend, with resistivity values ranging from about 25000 W · m to 500000 W · m. These results have been interpreted as the effect of a sharp transition from "marine ice" to "continental" ice an interpretation that is consistent with the results of surface mapping. Interpreting the Vertical Electrical Soundings (VES) is a complex process. In fact, the alternating layers of ice with different compositions and salt content generate great uncertainty relative to the corresponding electric stratigraphies. To solve these problems of equivalency, all the available constraints were used including the drilling thickness, seismic reflection profiles as well as radar profiles. The results were used to provide what is mainly a qualitative overview that is coherent with the glaciological hypotheses relative to the evolution and structure proposed by some researchers for this ice shelf.